Pengembangan Bahan Ajar Pendidikan Agama Islam Di SMPN 3 Sumberasih Satu Atap - Afkarina, zida afkarinah; Imam Bukhori; Mohamad Solihin (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2024)
The role of teachers is very important in education, teachers must be able to combine material, to create effective, efficient and enjoyable learning. Availablity of teaching materials to support the learning process to achieve goals. The aim of this research is to develop teaching materials with the constraints of minimal time allocation in infrastructure in a learning context. The method used uses a qualitative descriptive research type. Data collection techniques are used by observation, interviews, etc. in situations where time and resources are limited an efficient and effective approach is necessary to ensure the availablity of relevant materials and continue learning. This research proposes a development strategy that utilizes technology, curriculum, adjustment and collaboration between teachers and students to overcome these obstacles. The evaluation results show that this approach succeeded in improving the quality of learning despite the existing obstacles. The practical implication of this research is the provision of guidance and resources that can assist education in developing responsive teaching materials, in situations of minimal time allocation and infrastructure.